2012
DOI: 10.12693/aphyspola.121.497
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Changes in Sulphur Oxidation States in Prostate Cancer Cells

Abstract: Prostate cancer cell lines along with selected organic and inorganic compounds used as references were studied with sulphur K-edge X-ray absorption near edge structure spectroscopy. The experiment was performed at the SUL-X beamline of the synchrotron radiation source ANKA, Karlsruhe (Germany). The sulphur was chosen for the studies because it is an essential biological element and out of many relevant factors, it is believed that it can take an important part in cancer transformations. The main goal was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The mapping technique used allowed us to localize all of these forms in different morphological parts of the tissue that was impossible in case of point measurements. Our results are similar to the ones obtained for cultured prostate cancer cell lines, 22,23 but give a larger view since in case of tissue we are dealing with different cell types and also with the components of extracellular matrix that gives us more complex image of sulfur biochemistry in living organism. Results obtained in presented studies demonstrate the need to perform experiments on various biological systems-from cell lines cultured in artificial conditions to complex tissue samples from patients.…”
Section: Discussionsupporting
confidence: 84%
“…The mapping technique used allowed us to localize all of these forms in different morphological parts of the tissue that was impossible in case of point measurements. Our results are similar to the ones obtained for cultured prostate cancer cell lines, 22,23 but give a larger view since in case of tissue we are dealing with different cell types and also with the components of extracellular matrix that gives us more complex image of sulfur biochemistry in living organism. Results obtained in presented studies demonstrate the need to perform experiments on various biological systems-from cell lines cultured in artificial conditions to complex tissue samples from patients.…”
Section: Discussionsupporting
confidence: 84%
“…Although the positions of the main features are identical in all spectra, they differ by the intensity. Preliminary analysis performed with the use of peak fitting method to determine the area under the peaks showed that the content of reduced sulfur forms does not vary much between cell lines but significant differences are present in the content of oxidized sulfur forms between cancerous and non-cancerous cells [6,8]. These preliminary results suggested that there might be changes in redox balance, and therefore, the detailed analysis by linear combination fit method was performed with the use of ATHENA software [61].…”
Section: Sulfur Speciation In Prostate Cancer Cell Linesmentioning
confidence: 97%
“…Ideal experimental method to identify such changes should be highly sensitive, specific, and characterized by as minimal as possible sample manipulation. The studies presented in this section take advantage of X-ray spectroscopy to study sulfur species in prostate cancer cell lines and tissue [6,8,55,56]. Sulfur is a key element in human organism.…”
Section: Studies Of Changes In Chemical Forms Of Sulfur In Case Of Prmentioning
confidence: 99%
See 2 more Smart Citations